Legal Analysis of the Protection of Community Rights in Agrarian Conflicts with Companies Holding HGU in West Bangka - Muhammad Rifki Nauvaldi; Abdul Rasyid Saliman (Jurnal Daulat Hukum, 2026)
This study aims to analyze legal protection for communities in agrarian conflicts with companies holding Land Use Rights (HGU) in West Bangka. Agrarian conflicts involving communities and corporations are complex issues that are not only related to legal aspects, but also concern social justice and the recognition of traditional rights. The research method used is normative legal research with a legislative approach and a case approach. The results of the study indicate that normatively, protection for communities has been accommodated in various laws and regulations, such as the 1945 Constitution and the Basic Agrarian Law. However, in practice, this protection has not been implemented effectively due to weak recognition of customary territories, overlapping permits, and unequal positions between communities and companies. In addition, the available dispute resolution mechanisms have not fully provided substantive justice for communities. Therefore, it is necessary to strengthen regulations and government commitment to ensure the protection of community rights more effectively and fairly.